Yellowstone Wildfires Increased Stream Ion Concentrations and Export - Isabella G. Sadler; Lusha M. Tronstad; Christine Fisher; Robert O. Hall; Todd M. Koel (Nitrogen, 2024)
Wildfires in the western U.S. have increased in severity and duration in recent decades. Severe wildfires can enhance the rates of nutrient mineralization, causing large exports of inorganic nitrogen and other ions from forests to streams. Measuring the degree to which streams respond to severe, stand-replacing wildfires is critical to estimate in ecosystems prone to disturbance. In 2003, two severe crown wildfires burned in Yellowstone National Park, WY, USA. We studied the extent to which these fires increased nitrogen (ammonium, nitrate and nitrite), sulfate, chloride, and total dissolved phosphorus concentrations and export in three watersheds prior to and during the first four years post-fire. We measured higher concentrations of most ions after wildfire, and nitrate and chloride concentrations increased the most, increasing > 1000 µg/L. Concentrations of nitrate (≤146 times pre-fire concentrations), total dissolved nitrogen (≤11 times), chloride (≤9 times), and total dissolved phosphorus (≤7 times) were higher four years post-fire than before the wildfires burned. Exports of nitrate (≤1392 times), sulfate (≤14 times), and chloride (≤37 times) were also higher after wildfire, while nitrite (≤2.9 times) and ammonium (≤6.4 times) increased to a lesser degree. Stream concentrations of most ions were higher in watersheds that had a larger percent of the area burned. Comparing ion concentrations in streams before and after severe wildfires provides critical information to managers as the climate warms and the frequency of fire-conductive weather increases.